ANALISIS POSTUR KERJA DAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDS) PADA PETANI(STUDI LITERATURE RIVIEW) - Cindy Yunika Safithry; Susilawati (CV. ADIBA AISHA AMIRA, 2024)
Musculoskeletal disorders (MSDs) are health problems involving the joints, muscles, tendons, skeleton, cartilage, ligaments and nerves. The level of MSDs from the mildest to the most severe will interfere with concentration at work, cause fatigue and will ultimately reduce productivity. The agricultural sector is one of the jobs that has a potential risk of musculoskeletal disorders that have an impact on health related to their work which can cause several diseases and permanent disabilities. This study aims to determine the relationship between work posture and musculoskeletal disorders (MSDs) in farmers. This research is a research in the form of Literature Review. Researchers conducted searches on several search engines including: Google Scholar, Pubmed using the keywords